Gamification in Scientific Approach to Improve Students' Learning Motivation - Seruni, Faras (Universitas Jambi, Magister Program of English Education Department, 2024)
Knowing the fact that students’ learning motivation in learning English is low. This research investigates the effects of using gamification in scientific approach to conduct English learning in class. This quantitative research used experimental design to know whether there is an effect of gamification on students’ learning motivation. The population of this research is students in SMP Negeri 6 Natar, however this research used purposive sampling to decide the sample to meet the needs of the research. A questionnaire was used to measure the students’ learning motivation by using the Likert scale. To analyze the data, the researcher used Repeated measure T-Test. The results suggest that there is a significant improvement in students’ learning motivation before and after treatment. The data implies that the pre-score of students’ learning motivation is mostly in the medium level then it shifted to the high level on the post-score. The results show that the implementation of gamification in scientific approach improves students’ learning motivation.